Effect of COVID-19 vaccine on blood glucose metrics in Arabic people with type 1 diabetes - Al-Ozairi, Ebaa; Irshad, Mohammad; Taghadom, Etab; Varghese, Anisha; Sojan, Litty; Alkandari, Jumana (Frontiers in Endocrinology, 2023)
Introduction People with diabetes are at a higher risk for coronavirus disease-19 (COVID-19) and hence are prioritized for vaccination. The aim of the current study was to investigate the effects of COVID-19 vaccination on blood glucose control in Arabic people with type 1 diabetes (T1D). Secondary aim was to compare the responses between the two vaccines approved for use in Kuwait. Method: This retrospective study compared ambulatory glucose metrics, using a continuous glucose monitoring device, measured for 14 days before, and 7 days and 14 days after, the first and second doses of the COVID-19 vaccine in Arabic people with Type 1 diabetes (T1D). We also explored possible links with vaccine type and other clinical characteristics. Glucose metrics calculated were time in range (TIR, 3.9–10mmol/L), time above range (TAR, 10.1- 13.9 mmol/L or >13.9 mmol/L), time below range (TBR, 3-3.9mmol/L or <3 mmol/L) and glucose variability (CV). Results: We enrolled 223 participants in the study. Over the 7 days period after the first vaccination dose there was a decrease in TIR (mean difference (SD) –1.9%±14.8%; p=0.05) and increase in TAR >10 mmol/L (2.2%±15.9%; p=0.04), with no effects on TBR. These effects were not seen after the second dose or 14 days after either dose. There was a decrease in CV over the 7 days period after the first (−1.2% ±7.4%; p=0.02) and second vaccine doses (−1.1%±6.9%; p=0.03), with no effects noted 14 days after either dose. In subgroup analysis similar effects on TIR and TAR were also seen in those who had received the viral vector-based vaccine, but not the mRNA-based vaccine, although the decrease in CV was seen in those who had received the mRNA based vaccine but not the viral vector-based vaccine. Conclusion: We found a temporary impairment in glucose control in the first 7 days, particularly among individuals receiving viral vector vaccines. The group receiving mRNA vaccine was likely to experience an increase in glucose levels above the target range. However, the temporary change in metrics appears to return to pre-vaccination levels after one-week post-vaccination. The effects on glycemic parameters were more neutral after the second dose.